What's in Your Culture? Embracing Stability and the New Digital Age in Moving Colleges of Health Professions Virtually during the COVID-19 Pandemic: An Experiential Narrative Review - Melanie Poudevigne; Erika S. Armstrong; Marisa Mickey; Michelle A. Nelson; Comfort N. Obi; Andrew Scott; Naquilla Thomas; Tamara N. Thompson (MDPI AG, 2022)
As traditional education transitioned from face-to-face interactions to virtual learning during the COVID-19 pandemic, faculty and staff in dental hygiene, nursing, and exercise science programs placed students at the center of every educational decision and promoted stability in learning with their commitments to excellence in teaching and the delivery of content using educational and communication technology. This experiential narrative review explains how faculty members and administrators addressed online education with technology specific to health professions and how universities managed to assist students with innovative services for mental health. It also provides an insight into how degree-specific academic personnel embraced technology-based hands-on activities in community health clinics and clinical laboratories, with sustainable and impactful lessons in equity, affordability, and transformative education. Finally, health administrators gather their top-10 leadership recommendations to continue moving forward during the pandemic and present a unique self-reflection on the process of caring considerations required for a successful experience for faculty members, staff, and students.